Loss-of-Function NUBPL Mutation May Link Parkinson's Disease to Recessive Complex I Deficiency - Eis, Peggy S.; Huang, Neng; Langston, J. William; Hatchwell, Eli; Schüle, Birgitt (Frontiers in Neurology, 2020)
Mitochondrial dysfunction has long been considered a strong contributor to Parkinson’s disease (PD). There is substantial evidence that decreased Complex I (CI) activity plays a central role in PD pathogenesis. Furthermore, mutations in the nucleotide binding protein-like (NUBPL) gene of the nuclear genome cause autosomal recessive mitochondrial CI deficiency in children. Here, in a genome-wide screen for copy number variants (CNVs) in a PD cohort, we found a sporadic PD case with a complex chromosomal rearrangement of the NUBPL gene on chromosome 14q12. This NUBPL mutation is identical to one previously reported in a CI deficiency patient. We therefore hypothesize that pathogenic NUBPL variants may increase the risk for PD analogous to variants in the glucosylceramidase beta (GBA) gene that increase the risk of developing PD in heterozygous carriers.